HIV and three dimensions of Wisdom: Association with cognitive function and physical and mental well-being: For: Psychiatry Research. (December 2020) - Vásquez, Elizabeth; Lee, Ellen E.; Zhang, Weihui; Tu, Xin; Moore, David J.; Marquine, María J.; Jeste, Dilip V.
Highlights: Wisdom, a personality trait with affective (compassionate), cognitive, and reflective dimensions, has been associated with greater well-being and health in the general population, but its role in the health of people with HIV (PWH) has not been examined. Total wisdom score, as well as affective (compassionate) and reflective wisdom dimensions, were positively related to physical and mental well-being both in PWH and HIV- subjects. Our findings point to a possibility that enhancing these dimensions of wisdom might improve health outcomes in PWH. Abstract: Wisdom is a unique human personality trait with cognitive, affective or compassionate, and reflective dimensions. We evaluated relationships of three specific dimensions of wisdom with cognitive function and physical and mental well-being in people with HIV (PWH) and HIV-negative (HIV-) participants. Subjects included 138 adults (61 PWH, 77 HIV-) from the San Diego community. Validated measures were used to assess wisdom and well-being. Cognitive function was assessed via the Montreal Cognitive Assessment. We conducted multivariate linear regressions to evaluate the associations of wisdom dimensions with cognitive function and physical and mental well-being. Compared to the HIV- group, PWH had lower mean scores on cognitive function, and physical and mental well-being, and cognitive and reflective dimensions of wisdom, but similar scores on affective or compassionate wisdom. Among PWH, higher total wisdom scores were associated with older age, lower likelihood of substance dependence, greater mental well-being, better cognitive function, higher resilience, social support, and optimism scores, as well as lower levels of perceived stress and nadir CD4 count. Our findings of an association of different dimensions of wisdom with physical and/or mental well-being in PWH would point to a possibility that enhancing these dimensions of wisdom might improve health outcomes in PWH.